The Effectiveness of Group Discussion Methods in Efforts to Instill Tawhid Values in Early Childhood at RA Az-Zahra - Hendrayani (MANDAILING GLOBAL EDUKASIA, 2025)
Instilling the values ​​of monotheism from an early age is an important aspect in the formation of children's character and morals. One method that can be used in the learning process is the group discussion method. This method provides an opportunity for children to actively participate, develop understanding, and strengthen the concept of monotheism through interaction with peers and educators. This study aims to analyze the effectiveness of the group discussion method in efforts to instill the values ​​of monotheism in early childhood at RA Az-Zahra. The research approach used is qualitative with a descriptive method. Data collection techniques are carried out through observation, interviews, and documentation. The subjects of the study were teachers and students at RA Az-Zahra. The results of the study showed that the group discussion method was effective in improving children's understanding of the concept of monotheism, such as knowing Allah as God Almighty, understanding His greatness through His creations, and instilling an attitude of gratitude and prayer. Group discussions allow children to express their thoughts, listen to the opinions of their friends, and gain a deeper understanding through concrete examples given by the teacher. In addition, this method also helps in building children's self-confidence and improving their communication skills. However, the effectiveness of this method is highly dependent on the active role of the teacher in guiding the discussion and creating a conducive and enjoyable learning environment for children. Thus, the group discussion method can be used as one of the effective learning strategies in instilling the values ​​of monotheism in early childhood. The implication of this study is the importance of improving teacher skills in managing group discussions and developing learning materials that are appropriate to the child's developmental stage. It is hoped that this method can continue to be applied and developed in Islamic religious learning at the early childhood education level.